Nitrous oxide decomposition over Al2O3 supported noble metals (Pt, Pd, Ir): Effect of metal loading and feed composition. Issue 2 (June 2015) - Pachatouridou, Eleni; Papista, Eleni; Iliopoulou, Eleni F.; Delimitis, Andreas; Goula, Grammatiki; Yentekakis, Ioannis V.; Marnellos, George E.; Konsolakis, Michalis
Graphical abstract